2020
DOI: 10.2478/sg-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Clonal variation in phenological synchronization and cone production in aPinus patulaseed orchard

Abstract: Synchronization between female receptiveness and pollen dispersal, and fecundity of clones influence effective population size and genetic diversity of germplasm produced in seed orchards. Our objective was to determine clonal variation in phenological synchronization and in cone production in a Pinus patula seed orchard. Two-year phenology data of female and male strobili from a sample of 31 clones, and of male strobili in trees from neighboring natural stands of the same species were used. Synchronization in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Monitoring data in a Korean pine seed orchard for five consecutive years showed that the fertility variation would impact the genetic diversity of seed crops and possible management options 14 . In some previous reports, the stability of fertility, phenological traits, and cone production in some tree species remained stable, and with little change from year to year, so we could make an early evaluation and selection of these traits 9,12,15,16 . An inverse report showed unstable cone production over time in a 1.5-generation seed orchard of P. koraiensis, indicating that continuous monitoring was necessary for making wise management proposals 17 .…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Monitoring data in a Korean pine seed orchard for five consecutive years showed that the fertility variation would impact the genetic diversity of seed crops and possible management options 14 . In some previous reports, the stability of fertility, phenological traits, and cone production in some tree species remained stable, and with little change from year to year, so we could make an early evaluation and selection of these traits 9,12,15,16 . An inverse report showed unstable cone production over time in a 1.5-generation seed orchard of P. koraiensis, indicating that continuous monitoring was necessary for making wise management proposals 17 .…”
mentioning
confidence: 91%
“…Studies on phenology and synchronization have contributed to evaluating the level of effective out-crossing and the condition of genetic diversity in seed orchard seed lots 2 . Phenology affects the frequency of gene exchange among clones and the genetic composition of seeds derived from seed orchards [8][9][10] . Previous studies have documented that phenological variation among clones reduces the effective population size, promotes selfing, and increases the risk of contamination 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a more comprehensive study is needed in different regions and years in future studies. Due to the annual and seasonal differences in the reproductive capacity of parents in seed orchards ( Funda et al., 2009 ; Muñoz-Gutiérrez et al., 2020 ), continuous observation of mating and florescence in seed orchards is greatly significant to the management and construction of seed orchards and the formulation of breeding policies. However, continuous observation is a laborious and costly study.…”
Section: Discussionmentioning
confidence: 99%
“…The mating pattern and genetic diversity level of seed orchards largely determine their adaptability, biological and abiotic resistance, and sustainability ( Grattapaglia et al., 2014 ; Chen et al., 2018 ). The mating pattern of a seed orchard is mainly caused by the variation of female and male fertility between parents ( Nielsen and Hansen, 2011 ), the difference in reproductive success rate ( Torimaru et al., 2012 ; Funda et al., 2016 ), the synchronization of the flowering period ( Li et al., 2011 ; Zhang et al., 2016 ; Muñoz-Gutiérrez et al., 2020 ), and the difference in pollen competitiveness ( Nikkanen et al., 2000 ; Aronen et al., 2002 ). However, mating patterns have become more complex due to their expected co-ancestry accumulation in advanced generation breeding programs and seed orchards ( Yang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%